2015
DOI: 10.1212/nxi.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal ablation of CXCR2 on oligodendrocyte lineage cells

Abstract: Background:Residual CXCR2 expression on CNS cells in Cxcr2+/−→Cxcr2−/− chimeric animals slowed remyelination after both experimental autoimmune encephalomyelitis and cuprizone-induced demyelination.Methods:We generated Cxcr2fl/−:PLPCre-ER(T) mice enabling an inducible, conditional deletion of Cxcr2 on oligodendrocyte lineage cells of the CNS. Cxcr2fl/−:PLPCre-ER(T) mice were evaluated in 2 demyelination/remyelination models: cuprizone-feeding and in vitro lysophosphatidylcholine (LPC) treatment of cerebellar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…Previously, members of our group (25) generated mice in which Cxcr2 was selectively ablated in oligodendrocytes. Similar to the findings for the animals that we report here, Cxcr2 was silenced within oligodendroglia in adult mice upon tamoxifen treatment (25). Employing toxin models of demyelination, the authors clearly showed enhanced remyelination in animals in which CXCR2 signaling in oligodendrocytes was inhibited, arguing for an important role for this chemokine receptor in influencing oligodendrocyte biology.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Previously, members of our group (25) generated mice in which Cxcr2 was selectively ablated in oligodendrocytes. Similar to the findings for the animals that we report here, Cxcr2 was silenced within oligodendroglia in adult mice upon tamoxifen treatment (25). Employing toxin models of demyelination, the authors clearly showed enhanced remyelination in animals in which CXCR2 signaling in oligodendrocytes was inhibited, arguing for an important role for this chemokine receptor in influencing oligodendrocyte biology.…”
Section: Discussionsupporting
confidence: 86%
“…Through EM analysis of the spinal cords of the experimental mice, we determined that an increase in the remyelination of axons occurred following targeting of CXCR2 and that this correlated with an increased myelin thickness compared to that in control animals. Collectively, these findings support the concept that targeted ablation of CXCR2 on oligodendroglia in adult mice may enhance the maturation of OPCs into myelin-producing oligodendrocytes (25,58).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations